Association Between Seropositivity for Antibody to Chlamydia-specific Lipopolysaccharide and Myocardial Infarction or Chronic Coronary Heart Disease in Japanese Population - Akimoto, Yoshinori; Yamaguchi, Hiroshi; Takaya, Junshi; Shimada, Kazunori; Daida, Hiroyuki; Mokuno, Hiroshi (Japanese Journal of Cardiovascular Disease Prevention, 2001)
Increased attention is given to the association between Chlamydia pneumoniae infection and coronary artery disease (CAD). However, there are few reports of investigations of this association in the Japanese population. We examined serum IgA and IgG antibodies to Chlamydia-specific lipopolysaccharide by enzyme-linked immunosorbent assay in 671 patients with CAD and 385 control subjects. CAD patients were divided into acute myocardial infarction [(AMI), n=174], old myocardial infarction [(OMI), n=174], and chronic coronary heart disease [(CCHD), n=323]. Compared with the control group, CAD group had significantly higher prevalence of seropositivity for IgA (25.5 vs. 16.1%, p<0.0005) and IgG (55.0 vs. 44.4%, p<0.001). AMI (IgA : 28.7% p<0.001, IgG : 60.9% p<0.0005) and OMI groups (IgA : 33.3% p<0.00005, IgG : 62.1% p<0.0005) had also significantly higher prevalence of both antibodies. However, CCHD group had no different prevalence of both antibodies (IgA : 19.5% p=0.2, IgG : 46.8% p=0.5). After adjusted for confounding factors, odds ratios (ORs) of seropositive antibodies for CAD were 1.62 (95% confidence interval (CI), 1.02-2.58, p<0.05) for IgA seropositivity, and 1.01 (95% CI, 0.70-1.45, P=0.6) for IgG seropositivity. Between AMI and control groups, ORs of seropositive antibodies for myocardial infarction (MI) were 2.37 (95% CI, 1.27-4.44, p<0.01) for IgA seropositivity, and 1.40 (95% CI, 0.82-2.38, p=0.2) for IgG seropositivity. Between OMI and control groups, ORs of seropositive antibodies for MI were 2.27 (95% CI, 1.20-4.29, p<0.05) for IgA seropositivity, and 1.46 (95% CI, 0.86-2.49, p=0.16) for IgG seropositivity. These results suggest that chronic infection of Chlamydia is associated with MI rather than chronic coronary atherosclerosis in Japanese population.